Effects of Theory-Based Behavioral Interventions on Physical Activity Among Overweight and Obese Female Cancer Survivors: A Systematic Review of Randomized Controlled Trials - Amerigo Rossi EdD; Ciarán Friel MS; Leeja Carter PhD; Carol Ewing Garber PhD (Integrative Cancer Therapies, 2018)
Purpose. To determine whether theory-based physical activity (PA) interventions for overweight and obese female cancer survivors lead to increased PA and improved health. Methods. This systematic review examined randomized controlled trials analyzing the impact of theory-based PA interventions on overweight and obese female cancer survivors through December 2016. Searches of 5 electronic databases revealed 10 articles that included 1351 participants who met the inclusion criteria. Results. Participants were primarily non-Hispanic white (74%-100%) breast or endometrial cancer survivors. Intervention characteristics and PA assessment tools varied greatly. Adherence (68%-99%) and retention (79%-100%) were relatively high. Social cognitive theory was utilized as the theoretical construct in 9 of the 10 studies. Home-based interventions led to small improvements in PA (Cohen’s d range = 0.25-0.31), whereas home-based plus center-based interventions led to moderate to large improvements (Cohen’s d range = 0.45-1.02). Only three of the studies assessed psychosocial behavioral processes associated with PA, and the results were mixed. Health-related outcomes included improvements in aerobic fitness (Cohen’s d = 0.32-1.1 in 5 studies), large absolute decreases in waist circumferences (>6 cm in 3 of 5 studies; Cohen’s d = −0.31 to −1.02), and no change in inflammatory biomarkers (in 2 studies). Only one serious adverse event (pelvic stress fracture) was attributed to the interventions. Conclusions. Theory-based PA interventions are safe and feasible for overweight and obese female cancer survivors. Interventions that include a center-based component showed moderate to large effect sizes for PA. Future studies should evaluate behavioral variables and more health-related clinical outcomes.